2014
DOI: 10.1155/2014/297060
|View full text |Cite
|
Sign up to set email alerts
|

Gender Expression, Sexual Orientation and Pain Sensitivity in Women

Abstract: Larger investigations of the psychophysiological relationships among sexual orientation, gender expression and pain sensitivity are warranted. These findings may have implications for differences in clinical pain sensitivity of lesbian and bisexual women compared with heterosexual women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Hence, previous research on sex differences in pain functioning (e.g., neurocognitive and behavioral processes) that did not include concurrent measurements of individuals’ relationship experiences may have missed corollary components of the nexus between biological sex and pain perception. The current findings are also important for highlighting potential within-sex correlates of social psychological functioning, such as gender identity [57-59], which may partly influence external pain perception irrespective of biological sex. Finally, the findings may be especially relevant for understanding sex differences in felt pain caused by extrinsic painful stimuli (e.g., surface, skin tissue damage).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, previous research on sex differences in pain functioning (e.g., neurocognitive and behavioral processes) that did not include concurrent measurements of individuals’ relationship experiences may have missed corollary components of the nexus between biological sex and pain perception. The current findings are also important for highlighting potential within-sex correlates of social psychological functioning, such as gender identity [57-59], which may partly influence external pain perception irrespective of biological sex. Finally, the findings may be especially relevant for understanding sex differences in felt pain caused by extrinsic painful stimuli (e.g., surface, skin tissue damage).…”
Section: Discussionmentioning
confidence: 99%
“…According to Franconi et al (2012), female patients are traditionally underrepresented in clinical studies, for different reasons not to elucidate here (e.g., Pinnow et al, 2009). On the other hand specifically in the area on pain, sex differences are well established, both for clinical and for experimental setting (Paller et al, 2009), but also have been found to be variable with sexual orientation and identity (Vigil et al, 2014). In the following sections we will review advances in research over the last decade, with respect to pain and placebo analgesia.…”
Section: The Short History Of Placebo Researchmentioning
confidence: 99%
“…This hypothesis is consistent with the currently observed correlations between women's subjective body impressions and variability in pain reporting. Numerous previous studies have likewise shown that variability in gender expression (e.g., trait masculinity/femininity and sexual orientation) and the manipulation of gender role expectations influence pain reporting (e.g., Defrin et al 2009;Robinson et al 2003;Vigil et al 2014b).…”
Section: Discussionmentioning
confidence: 88%